Marketing Strategy to Improve Sales Growth in Imah Nini Bogor - Anshari, Anisah; Aditya Wibowo, Satya (The Indonesian Journal of Business Administration, 2017)
Abstract. Imah Nini is a company that specialized on selling Bogorâ€™s steamed sponge form of tubers. Started his business by selling cakes at home, Imah Nini at this time has expanded its business by opening a new pastry shop in the business district in the city center of Jl. Pajajaran No. 1 V-Point office block qz. The company set sales goal every month by selling at least 100 boxes per day in hope that they can return back their capital in time. Although Imah Nini sales did increase every month, for the owner the sales increase really slow and barely reach they sales target every month. The purpose of this study is to provide effective business solutions to existing problems. Methods of research conducted by the author divided into internal and external analysis where the author conducted with the owner Imah writer Nini Ny. Arie Latifah SH and the staff in each division, the author is also distributing questionnaires to the respondents around the store Imah Nini to complete the data analysis by the author. Internal analysis is done by using STP and Marketing Mix to know the basic business activities Imah Nini today. External analysis done by using PESTEL, Porter's Five Forces, and Competitor Analysis to find out how Imah Nini facing any external forces and also to learn more about the customer point of view towards the brand. For the business solution the author will draw a conclusion of marketing strength and weakness from internal analysis, and also marketing thread and opportunity from external analysis. The result from this study shows that Imah Nini current marketing condition is their STP need to be re-positioned again and the best effective strategy for the business right now is by organizing marketing program and advertising based on factor marketing mix 7p with corresponding market STP that has been proposed as a solution by the author.Â Keywords: Imah Nini, Marketing Mix, PESTEL, STP, SWOT